The role of arousal in the spontaneous regulation of emotions in healthy aging: a fMRI investigation - Dolcos, Sanda; Katsumi, Yuta; Dixon, Roger A. (Frontiers in Psychology, 2014)
Despite ample support for enhanced affective well-being and emotional stability in healthy aging, the role of potentially important dimensions, such as the emotional arousal, has not been systematically investigated in neuroimaging studies. In addition, the few behavioral studies that examined effects of arousal have produced inconsistent findings. The present study manipulated the arousal of pictorial stimuli to test the hypothesis that preserved emotional functioning in aging is modulated by the level of arousal, and to identify the associated neural correlates. Young and older healthy participants were presented with negative and neutral pictures, which they rated for emotional content, while fMRI data were recorded. There were three main novel findings regarding the neural mechanisms underlying the processing of negative pictures with different levels of arousal in young and older adults. First, the common engagement of the right amygdala in young and older adults was driven by high arousing negative stimuli. Second, complementing an age-related reduction in the subjective ratings for low arousing negative pictures, there were opposing patterns of activity in the rostral/ventral anterior cingulate cortex (ACC) and the amygdala, which showed increased vs. decreased responses, respectively, to low arousing negative pictures. Third, increased spontaneous activity in the ventral ACC/ventromedial prefrontal cortex (vmPFC) in older adults was linked to reduced ratings for low arousing negative pictures. Overall, these findings advance our understanding of the neural correlates underlying processing of negative emotions with different levels of arousal in the context of enhanced emotional functioning in healthy aging. Notably, the results support the idea that older adults have emotion regulation networks chronically activated, in the absence of explicit induction of the goal to regulate emotions, and that this effect is specific to low arousing negative emotions.